1984
DOI: 10.1063/1.864747
|View full text |Cite
|
Sign up to set email alerts
|

Observation of magnetic fields in laser-produced plasma using the Zeeman effect

Abstract: The self-generated magnetic field produced when a pulsed Nd:glass laser is focused onto a carbon foil target is measured for the first time using the Zeeman effect. Emission from the CV 1s2s3S1–1s2p3P2 (2270.9 Å) was used for the measurement. At a laser irradiance of ∼5×1012 W/cm2, the magnetic field increased from 100 to 200 kG when the focal spot was changed from a flat-topped distribution to a ring pattern, which caused higher density gradients. A Faraday rotation measurement at approximately 200 kG agreed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…(50). Figures 18, 19 and 20 (example taken from Mc Lean [55,56]) show that the results are quite close to the exact calculation. The main approximation here comes from the fact that g e is replaced by its average value in LS coupling, which is justified in case of very strong magnetic fields (Paschen-Back effect).…”
Section: Approximation Of the Coefficient G Esupporting
confidence: 63%
“…(50). Figures 18, 19 and 20 (example taken from Mc Lean [55,56]) show that the results are quite close to the exact calculation. The main approximation here comes from the fact that g e is replaced by its average value in LS coupling, which is justified in case of very strong magnetic fields (Paschen-Back effect).…”
Section: Approximation Of the Coefficient G Esupporting
confidence: 63%
“…An alternative magnetic-field diagnostic, the Zeeman splitting and broadening of spectral lines, was demonstrated by McLean et al 571 and found to give results consistent with Faraday rotation measurements. The diagnostic gives an average magnetic field along the line of sight.…”
Section: F Self-generated Magnetic Fieldssupporting
confidence: 59%
“…A numerical estimate for the maximum cross section is (12) o Here the wavelength A is an A units and A is the atomic weight of the absorbing atom or ion. Depending on the densities N in the (13) where g is again the Gaunt factor (g ~ 1, 64ana 2 /3 3 / 2 ~ 0.88 x n 0 10-16 cm 2 ). This process is, of course, the inverse of recombination, whereas there is no special term for absorption by inverse bremsstrahlung which is important in laser-matter interactions.…”
Section: Radiative Transportmentioning
confidence: 99%
“…Zeeman splittings in strong and reasonably homogeneous fields have, however, been observed in a plasma focus experiment [15] and in laser-produced plasmas [13]. Since broadening due to thermal Doppler effects and mass motion and also from opacity are competing with Zeeman effects, it is necessary to perform line profile and structure measurements with polarizing optics and to look for small differences in the corresponding spectra.…”
Section: Magnetic Fieldsmentioning
confidence: 99%